2011
DOI: 10.28945/1462
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking and Teaching: An Australian Case Study

Abstract: In recent years, the Internet has impacted all aspects of modern society. We have now seen the phenomenon of social networking and the impact that this had upon all aspects of modern society including higher education. An issue is how can these social networking technologies relate to tertiary education and how can they be used in this educational context. This paper is based on two case studies which were conducted at an Australian University into the usage of two social networking systems in a teaching envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…A Meta research of 21 papers on microblogging in education revealed potential for collaborative learning, sharing resources, learning any time any place, informal communication between students and between students and teachers, and enhancing students engagement. On the other hand, limitations of microblogging were mentioned, such as unfamiliarity of students with Twitter, students are not convinced of its benefits, and the length limit of text influences depth of dialog (Gao, Luo & Zhang, 2012;Leitch & Warren, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A Meta research of 21 papers on microblogging in education revealed potential for collaborative learning, sharing resources, learning any time any place, informal communication between students and between students and teachers, and enhancing students engagement. On the other hand, limitations of microblogging were mentioned, such as unfamiliarity of students with Twitter, students are not convinced of its benefits, and the length limit of text influences depth of dialog (Gao, Luo & Zhang, 2012;Leitch & Warren, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Facebook-Groups have potential for group collaboration (Fewkes & McCabe, 2012;, promotion of social interaction , promotion of interaction between students and teachers , and expansion of learning beyond the classroom (Fewkes & McCabe, 2012;. Limitations of this tool are privacy matters Wang, Woo, Quek, & Liu, 2012), students are distracted while using it for learning (Fewkes & McCabe, 2012;Leitch & Warren, 2011), teachers lack implementation knowledge (Fewkes & McCabe, 2012), and the fact that the discussions are not organized (Wang, Woo, Quek, & Liu, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impacts of social media use as a learning tool have also been explored in literature, Facebook helps improve social contact, group collaboration, and communication between learners and lecturers, reported by Fewkes and McCabe (2012) and Wang, Woo and Quek (2012). Twitter, to the contrary hand, offers potential that is comparable, yet students report that due to the character limit for text messages, conversations on Twitter tended to be limited (Gao, Luo & Zhang, 2012;Leitch & Warren, 2011).…”
Section: Instant Messagingmentioning
confidence: 99%
“…They are born into a world of technology and hence demonstrate a different approach to life, socialization, the perception of knowledge, and decision making compared to the previous generations (Artemova, 2018, p.8). Although this approach is attributed to technological developments, (Leitch and Warren, 2011), it is essential to understand their aims of using the existing technologies. Gezgin, Hamutoğlu, Samur and Yildirim (2018) showed that mobile devices are predominantly used for accessing the social media.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%